PENGARUH PENGAWASAN TERHADAP PENINGKATAN PRODUKTIVITAS KARYAWAN PADA PT. SIMPATIK CITRA ADI SARANA UNAAHA KABUPATEN KONAWE - Bindarto Bindarto (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2020)
This study aims to analyze the effect of supervision on increasing employee productivity at PT Simpatik Citra Adi Sarana Unaaha Konawe District. Data collection methods used are the method of observation, documentation, and questionnaires. The analytical method used is a simple linear regression analysis. Based on the discussion of the results of research that has been done, conclusions can be drawn relating to the effect of supervision on increasing employee productivity of PT Simpatik Citra Adi Sarana Unaaha Konawe Regency that the influence of supervision has a role and relationship to increasing employee productivity at PT Simpatik Citra Adi Sarana Unaaha Konawe Regency.